Pengelolaan Konten Digital dalam Meningkatkan Engagement pada Media Sosial SCTV - Nurulisa Fitri Wahyuni; Wahyu Budi Priatna (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This internship research aims to examine the content management strategies implemented by SCTV’s Social Media Division to increase engagement on its Instagram account, @sctv. The study was conducted during the internship period using observation, active participation, interviews, and literature review. The findings show that content management involves insight research, brainstorming, format selection, and differentiation between promotional and entertainment content. Reels featuring trending actors generate the highest engagement. Key factors influencing engagement include content relevance, posting consistency, content curation, two-way interaction, and data-driven evaluation through A/B testing. The study concludes that structured, adaptive, and analytics-supported strategies effectively improve Instagram engagement for SCTV.